Social Action after the Palu Natural Disasters in Max Weber's Perspective - Nole, Otniel Aurelius; Sinaga, Dearni Nurhasanah (FISIP UIN SGD Bandung, 2025)
On September 28, 2018, Palu experienced one of the most significant natural disasters in its history, consisting of three types of catastrophes: earthquakes, tsunamis, and liquefaction. Natural disasters have severe impacts, but life continues through the ability to engage in social action. This research analyzed social action in the aftermath of the Palu disaster from Max Weber’s perspective. A qualitative method with a literature review approach was used. The researchers examined articles from journals, conference proceedings, and book chapters retrieved from databases such as Sinta, Scopus, DOAJ, and Google Scholar. These sources were then analyzed and discussed using Max Weber’s books on social action theory. The research found that social action after the Palu disaster is categorized into five ideal types: instrumental rational action, value-rational action, emotional action, traditional action, and communal-conscious action. Each ideal type reflects unique characteristics. The actors play a crucial role in rebuilding Palu, contributing to recovery, development, and empowerment. Contribution: This article sociologically presents depictions of the behavior of the Palu community after natural disasters from the perspective of a social theory. Using this framework, the researchers analyze how the people of Palu engage in social action following the disasters, emphasizing the collaborative efforts of social actors in driving transformation over time. This transformation empowers the community to rebuild their lives, strengthen resilience, and work toward a more sustainable and adaptive future in the face of ongoing and future challenges.